The problem of the Russian Federation image formation by German think tanks in the context of the Syrian crisis (case of Friedrich-Ebert-Stiftung) - Ivkina, N.V. (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ Mezhdunarodnye otnosheni͡a, 2018)
The relevance of the research topic due to the ever-increasing role of the analytical institutions in the process of formation of Russia’s image in the public consciousness. In this context, the position of Germany represents the greatest interest. Germany is a state, on the one hand, a NATO member, on the other hand, represents one of the main European partners of Russia. This prevents it to form a clear-cut stance on issues directly related to Russia and Germany, on issues in solving which involved both countries. The aim of the study is to identify the role of think tanks of Germany in the process of forming the image of Russia, and also the degree of influence of research and analytical centers on the media. The subject of research was the problem of the Syrian crisis. For example, the Friedrich Ebert Foundation implemented a study to identify interest centers in shaping the image of Russia in the framework of solving the Syrian crisis. As research methods is to provide a description method used for studying the materials of the Fund, the method of comparison for the choice of the object of study, and to determine the effect of center content on various media. For wider exploration of topics in addition to the materials analytical centers were used for more of the Russian and foreign literature, as well as the materials of the statistical agencies. The results of the study represent a number of conclusions, which show the degree of interest of the Friedrich Ebert Foundation in the process of formation of Russia’s image and prospects of implementing the ideas of the analytical center in the German news system.